Nonlinear Solution of a Piezoelectric PN Junction under Temperature Gradient - Guo, M.K.; Qin, G.S.; Lu, Chunsheng; Zhao, M.H. (2022)
By considering the nonlinear coupling of piezoelectricity, thermoelectricity and pyroelectricity, this paper investigated the polarization effect related to temperature gradient in a thermo-piezoelectric PN junction. The analysis is based on a perturbation method and the one-dimensional nonlinear theories of thermo-piezoelectric semiconductors. It is shown that as thermal load increases, the linear solution gradually separates from the nonlinear one, in which the third-order solution is basically coincident with the nonlinear numerical solution of COMSOL. It is found that the electromechanical fields, carrier transport characteristics and turn-on voltage have a fast response to temperature gradient. By using the perturbation method, the approximate nonlinear solution of a thermo-piezoelectric PN junction can be obtained. Furthermore, the possibility of thermal manipulation is evident in a piezoelectric PN junction. These findings will be instructive to a good understanding of the electromechanical coupling characteristics of a PN junction and beneficial to development of a new method for its property modulation.